Self-Assembling Peptides as Extracellular Matrix Mimics to Influence Stem Cell's Fate - Hellmund, Katharina S.; Koksch, Beate (Frontiers in Chemistry, 2019)
Interest in biologically active materials that can be used as cell culture substrates for medicinal applications has increased dramatically over the last decade. The design and development of biomaterials mimicking the natural environment of different cell types, the so-called extracellular matrix (ECM), is the focus of research in this field. The ECM exists as an ensemble of several adhesion proteins with different functionalities that can be presented to the embedded cells. These functionalities regulate numerous cellular processes. Therefore, different approaches and strategies using peptide- and protein-based biopolymers have been investigated to support the proliferation, differentiation, and self-renewal of stem cells, in the context of regenerative medicine. This minireview summarizes recent developments in this area, with a focus on peptide-based biomaterials used as stem cell culture substrates.